PENGARUH E-SERVICE QUALITY TERHADAP KEPUASAN TAMU MENGINAP DI OYOROOMS KOTA BUKITTINGGI - Nidia Wulansari; Dwi Pratiwi Wulandari (Ensiklopedia of Journal, 2021)
The purpose of this study was to analyze the influence of E-Service Quality on guest satisfaction during the stay at Oyorooms in Bukittinggi. This type of research is a causal associative that determines the effect of E-Service Quality on guest satisfaction during the stay at Oyorooms in Bukittinggi. The population in this study were guests who had stayed at Oyorooms in Bukittinggi and using Oyorooms application, with the total sample were 55 people by using incidental sampling techniques. Data analysis technique used was simple linear regression analysis by analyze the influence of E-Service Quality on guest satisfaction during the stay at Oyorooms in Bukittinggi. The results showed that: There is a significant influence between E-Service Quality on guest satisfaction during the stay at Oyorooms in Bukittinggi. E-service Quality has a score of 3,92. It shows the quality of e-services provided by oyorooms is good. The main thing to consider for guests who make room bookings on the oyorooms website, it's efficiency. The oyorooms website can be accessed and used easily. That way guests who are satisfied with oyorooms services are willing to recommend oyorooms to other potential guests because it has good online services.